The Cost of the Veil: Visual Communication Impacts of Hijab on News Judgments. Issue 6 (2nd November 2019) - Connolly-Ahern, Colleen; Ahern, Lee; Coman, Ioana Alexandra; Molina Davila, María Dolores; Davis, Stefanie E.; Cabrera-Baukus, María
Abstract : Using disposition theory as a framework, this 2 (headscarf vs. no headscarf) by 2 (US citizen vs. refugee) experiment sought to elucidate the impact of visual and verbal cues in mediated messages on conclusions drawn from a television news package about a woman accused of consorting with a known terrorist group in the US, in terms of parochial empathy for and perceived innocence of the woman. Parochial empathy measures the difference between ingroup and outgroup empathy; higher levels indicate ingroup empathy is greater than outgroup empathy, meaning the individual's empathy is very narrow in scope or "parochial." Political identity was a measured independent variable. The data supported a model in which political identity was a significant moderator of the headscarf's effect on parochial empathy, and that parochial empathy mediated the relationship between the manipulated and measured predictor variables on perceived innocence. Details of the relationships among variables are reported and the implications for theory and journalism practice are discussed.